A Review of Di-(2-ethylhexyl) Phthalate (DEHP) Exposure and Metabolic Syndrome in Adults - Daramusseng, Andi; Sulistiyani; Suhartono; Darundiati, Yusniar Hanani (Poltekita: Jurnal Ilmu Kesehatan, 2025)
The sources of DEHP exposure are very wide because it is used as a plasticizer and additive in cosmetics and personal care products. Epidemiological studies have shown that DEHP and its metabolites can increase the risk of metabolic syndrome. However, this observation is still debated. Therefore, we conducted a systematic review aimed to investigate the relationship between DEHP exposure and metabolic syndrome in adults. This study used three databases, namely Pubmed, Scopus, and ScienceDirect, with English-language publications from 2019 to 2024. Seven cross-sectional and cohort studies from South Korea, the United States, Mexico, and Taiwan met the inclusion criteria selected through the PRISMA stages They were assessed for quality using the JBI Critical Appraisal Tool. The findings showed that only studies conducted in the United States and South Korea showed a significant association between DEHP and its metabolites (MEHP, MECPP, MCMHP, MEHHP, and MEOHP) with metabolic syndrome. However, these findings were limited to men, white men, premenopausal women, and postmenopausal women. In conclusion, DEHP and its metabolites showed inconsistent results on metabolic syndrome in adults. Recommendations are that further studies are needed with more robust designs in the future in various countries to clearly describe the relationship between DEHP and metabolic syndrome and strong regulation of phthalate use to minimize exposure.